Problem solving steps in online PBL - Shahbodin, Faaizah; Bakar, Norasiken; Mohd Bakri, Nurhazirah (2010)
Problem Based Learning is a well known learning method that will start the learning by giving the problem as the appetizer of the learning process. Teh existence of online PBL invites researchers to produce more creative learning system. This paper will discuss about the research framework for development of Online PBL IT Security subject. The design of the testing method also will be discussed here. Finally the storyboard design of the prototype will also be highlighted.